Teachers’ perceptions on identifying and catering to the needs of mathematically gifted and talented students - Ayebo, Abraham (Penerbit Universiti Kebangsaan Malaysia, 2016)
Giftedness is an elusive concept. The way teachers perceive the meaning of giftedness affects how they teach and attend to the needs of the gifted students in their classrooms. The aim of this study was to examine teachers’ views on teaching mathematics to gifted/talented students. The methodological orientation of the study was phenomenological. This qualitative study reports the perceptions of teachers who teach mathematically gifted and talented students on perceived characteristics of mathematical giftedness as well as how to cater to the needs of such students. Interviews were conducted with five teachers who teach mathematics to gifted and talented students. Some of the findings include distinction between gifts and talents, student subgroups and instructional needs of mathematically gifted students.